Comparative Assessment of Brewery Wastewater Treatment Potential by Microalgae Parachlorella kessleri and Chlorella vulgari - Kalantaryan, N. K.; Harutyunyan, B. A.; Minasyan, E. V.; Tsaturyan, A. H.; Pavlečić, M.; Marđetko, N.; Goginyan, V. B. (Հայաստանի ԳԱԱ «Գիտություն» հրատ.)
The possibility of brewery wastewater treatment by Parachlorella kessleri and Chlorella vulgaris microalgae strains and the efficiency of wastewater treatment depending on different concentrations of inoculum volume have been studied. The prospects of using brewery wastewater as a substrate for fatty acids production were also investigated in the framework of this research. Ուսումնասիրվել է գարեջրի արտադրության թափոնների մաքրման հնարավորությունը Parachlorella kessleri և Chlorella vulgaris միկրոջրիմուռների շտամների օգնությամբ, ինչպես նաև հոսքաջրերի մաքրման արդյունավետությունը՝ կախված ինոկուլատի տարբեր ծավալներից: Հետազոտվել են նաև գարեջրի արտադրության թափոնների կիրառման հեռանկարները՝ որպես ճարպաթթուների արտադրության սուբստրատներ։ Изучена возможность очистки сточных вод пивоваренных заводов штаммами микроводорослей Parachlorella kessleri и Chlorella vulgaris, а также эффективность очистки сточных вод в зависимости от различных концентраций объема инокулята. Также исследованa возможность использования сточных вод пивоваренного производства в качестве субстрата для производства жирных кислот в рамках данного исследования.
Keywords: Biophysics; Biotechnology